A comparative study between laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation and conventional (Milligan-Morgan) hemorrhoidectomy - Rajkumar Verma; Narendra Kumar; Vipin Mishra (Asian Journal of Medical Sciences, 2024)
Background: Hemorrhoids have a much higher incidence than rectum and colon diseases worldwide. The prevalence was estimated to be between 2.9% and 27.9% among the worldwide population, of which 4% are symptomatic. Based on the Gauss method, the highest incidence was present in patients aged between 45 and 65 years.